The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.20944/preprints202003.0062.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Market Channel Preference Among Smallholder Cocoyam Farmers in South Africa: A Food Security Perspective

Abstract: Market channel choice makes important contributions to the incomes and other livelihood attributes among smallholder farmers in developing countries. Often considered from a number of perspectives, the dominant view articulated suggests an advantageous integration into formal market channels. This position is questioned as it has implications for smallholder farmers’ food security and rural incomes. Using a mixed methods approach, the study collected primary data from 174 smallholder farmers and appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…This finding implies that about 84.5% of the total cocoyam produced in the study area is marketed and consumed within the vicinity. This finding is in agreement with Nwafor (2018), who found that 89% of the respondents use the farm gate as their major marketing channel. This is an evidence of subsistence nature and low scale production by rural farmers as asserted by Udoh, and Akpan, (2015).…”
Section: Marketing Channel Of Cocoyam Farmerssupporting
confidence: 92%
“…This finding implies that about 84.5% of the total cocoyam produced in the study area is marketed and consumed within the vicinity. This finding is in agreement with Nwafor (2018), who found that 89% of the respondents use the farm gate as their major marketing channel. This is an evidence of subsistence nature and low scale production by rural farmers as asserted by Udoh, and Akpan, (2015).…”
Section: Marketing Channel Of Cocoyam Farmerssupporting
confidence: 92%
“…As food security issues are increasing, sustainable agriculture has become a concern for governments, policymakers, and researchers alike. Past studies have highlighted that small farmers are the key to solving economic issues (Nwafor, 2020;Mariyono et al, 2019) involving unemployment, hunger, and poverty in rural areas (Mmbando et al, 2017). However, the measurement of the small farmers' sustainability is still at an early stage and not ultimately measured.…”
Section: Problem Statementmentioning
confidence: 99%
“…The supply chain participants will function more sustainably when there is trust in their relationships. Likewise, Nwafor (2020) points out that the relationship among the members in the market channel needs to be highlighted as it is a critical factor for a business.…”
Section: Trust and Commitment Affect On Small Farmer Sustainability P...mentioning
confidence: 99%
“…The case of smallholder farmers in South Africa is worth exploring, due to the acclaimed disparity within the agricultural sector (Nwafor, 2015) as well as the perception regarding the inflexibility of the economy to engage and reward previously marginalized emerging farmers (Chikazunga and Paradza, 2012). This has discouraged many smallholder farmers from accessing formal markets, leading to their engagement with alternative informal channels for marketing (Nwafor, 2020).…”
Section: Introductionmentioning
confidence: 99%